The traditions of realism in the literary and philosophical concept of M.M. Filippova - S. Ivanova, Anna (2019)
Mikhail Mikhailovich Filippov - the Great Russian writer, literary historian, representative of the "natural school". In his works, Filippov talks about the role of art in human life. Filippov calls deduction as the main method of knowing reality. The basis of the works of art M.M. Filippova has an illusion that elevates reality.